Research Hotspots and Trends of Exercise on Parkinson's Disease: A Global Bibliometric Analysis From 2012 to 2021 - Chen, Ji-Wei; Du, Shu-Hao; Chen, Tian-Cong; Zhu, Kun (Frontiers in Human Neuroscience, 2022)
Background: Parkinson’s disease is a chronic neurodegenerative disease, which can be alleviated in drug treatment, but with evident side effects. At the same time, increasing evidence shows that exercise can significantly improve the symptoms of patients with Parkinson’s disease, with an effect that cannot be achieved by drug treatment. The related research on exercise on Parkinson’s disease increases rapidly with the passage of time. However, the research analysis on Parkinson’s disease by means of bibliometrics is rare. The purpose of this study is to perform a bibliometric analysis of the research hotspots and development trends of the global movement on Parkinson’s disease from 2012 to 2021. Methods: The literature was derived from the Web of Science core collection database, and the social science citation index was set as SCI-EXPANDED. The language was set to English, and the literature category was set as article and review and published from 2012 to 2021. CiteSpace and other software were used to analyze the relationship among published documents, countries, institutions, journals, authors, references, disciplines, and key words. Results: A total of 2222 articles were included in the analysis. The analysis showed that the publication volume increased with the increase in years, with a total of 76 countries and 546 academic journals published; the largest number was that of the United States. The journals are mainly concentrated in the fields of neurology, sports and ophthalmology. Rush University and MOVEMENT DISORDERS journals are the main institutions and journals. The cited keywords show that trial, cognition, and interference are the research hotspots and development trends in recent years. Conclusion: The number of published articles on Parkinson’s disease by exercise has increased rapidly in the past ten years, and the bibliometric analysis can provide useful information for future research teams and researchers.